Resources of Digital FIR Filters Hardware Implementation in FPGAs for Digital Image Processing in Real Time - Peter Kulla (Advances in Electrical and Electronic Engineering, 2004)
The main image information content, from the human visual system viewing point, is focused into whole colorimetric and spatial informations. Because every image is result of some previous processes, the goal for all standard image processing methods is improvement colorimetric and spatial image parameters in relation maximum information content by the complicated and expensive systems for digital image processing in (quasi)real time [1] based on the flash signal (multi)processors. Some single-purpose applications do not need the robust and flash systems for DIP and be enough for their use single digital filters with suitable hardware implementation. In the contribution discussed problem is therefore focused on the short description of FIR digital tilters and their hardware implementation in FPGAs-Xilinx for usage in the image processing in real time include obtained experimental results.